If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + -13 = -4z + 14 Reorder the terms: -13 + 5z = -4z + 14 Reorder the terms: -13 + 5z = 14 + -4z Solving -13 + 5z = 14 + -4z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4z' to each side of the equation. -13 + 5z + 4z = 14 + -4z + 4z Combine like terms: 5z + 4z = 9z -13 + 9z = 14 + -4z + 4z Combine like terms: -4z + 4z = 0 -13 + 9z = 14 + 0 -13 + 9z = 14 Add '13' to each side of the equation. -13 + 13 + 9z = 14 + 13 Combine like terms: -13 + 13 = 0 0 + 9z = 14 + 13 9z = 14 + 13 Combine like terms: 14 + 13 = 27 9z = 27 Divide each side by '9'. z = 3 Simplifying z = 3
| 3x+12=6x-9x-12 | | 4(8-d)-50=20d-6(3+4d) | | y=sqrt(18x+9) | | 7x-2(x-6)=3 | | 3x+2=5y | | 4(x-5)+11=3(x+2)-3 | | 5(x+0.4)=5 | | 5x+11+119=180 | | 7(2x-1)=3 | | 3+13=2x | | y=5x+11+119 | | -12(3x+5)= | | 2.1x+55.9=10.0-13.2x | | 10x=5(x-11) | | -59-2x=13-10 | | 3n+(1-n)-n=-6 | | 45z-90z= | | 6x[5x-7]=432 | | x+1=44 | | 13-9x=51-2x | | 7a+9b= | | 3(a-2)+5w=22 | | 2x^3+5x^2-12=0 | | -19-9x=10x+23 | | 3m+4-9m=-9-6m+23 | | 16x-8=14x+4 | | 3(3+6x)-3=114 | | 6-68= | | 68-6= | | 5x+2(6x-8)=120 | | 17.92=x-0.2x | | 35e+23-30e=48 |